2017
DOI: 10.1371/journal.pone.0169958
|View full text |Cite
|
Sign up to set email alerts
|

Lead Exposure Induces Weight Gain in Adult Rats, Accompanied by DNA Hypermethylation

Abstract: ObjectivePrevious studies have revealed the association of lead (Pb) exposure with obesity. DNA methylation alteration has been suggested to be one of the regulatory mechanisms of obesity. We aimed to explore whether Pb exposure is related with weight gain and DNA methylation alteration.MethodsMale adult 8 week Wistar rats were divided into 5 groups: the normal chow diet (NCD); the NCD+0.05%Pb; the NCD+0.15%Pb; the NCD+0.45%Pb and the high fat diet. Rats were exposed to different dosages of Pb through drinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 36 publications
3
17
0
1
Order By: Relevance
“…This study suggests that combination of all solanum malongen, carrots subsp.sativus and solanum lycopersicon is suspected to properly reverse internal abnormality or injury resulting in weight loss in lead induced toxicity but may not properly normal the blood glucose level. Hence, in case of where hyperglycemia treatment is done using standard drugs, the administration of all three juices extract will help heal internal injuries but where injury is not yet sustained just insulin resistance, carrots subsp.sativus and solanum lycopersicon juice extract will be best for regulation of such lead induced hyperglycemia (Sun et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This study suggests that combination of all solanum malongen, carrots subsp.sativus and solanum lycopersicon is suspected to properly reverse internal abnormality or injury resulting in weight loss in lead induced toxicity but may not properly normal the blood glucose level. Hence, in case of where hyperglycemia treatment is done using standard drugs, the administration of all three juices extract will help heal internal injuries but where injury is not yet sustained just insulin resistance, carrots subsp.sativus and solanum lycopersicon juice extract will be best for regulation of such lead induced hyperglycemia (Sun et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, changes in weight gain, glucose intolerance and insulin resistance in the STD+500 ppm Pb animals approximated those observed in animals fed a HFD only. No significant changes in hyperglycemia were observed with Pb exposure(53). Whole genome bisulfite sequencing of liver tissue from STD+500 ppm Pb animals revealed hypermethylation at the whole genome level and differentially methylated genes were enriched in pathways involved in lipid and glucose metabolism.…”
Section: Lead (Pb)mentioning
confidence: 95%
“…Cultured islets of Langerhans exposed to Pb had decreased cell viability and glucose-stimulated insulin secretion as well as altered markers of endoplasmic reticulum stress (e.g., glucose regulated protein 78 (Grp78), nuclear factor kappa-light-chain-enhancer of activated B cells (Nfkb), and CCAAT/enhancer-binding protein homologous protein (Chop), and increased baseline insulin levels, glycogen synthase kinase 3 beta ( Gsk3b ) activity, and ROS production. In another study, adult male rats (8 weeks) were exposed for 21 weeks to a STD without or with Pb (500, 1500 or 4500 ppm) administered via drinking water, or to HFD alone(53). STD+500 ppm Pb animals exhibited significantly greater weight gain, as well as fasting glucose and insulin levels, HOMA-IR, TGs and glucose intolerance compared to all other STD±Pb animals.…”
Section: Lead (Pb)mentioning
confidence: 99%
“…It is known that heavy metals, including lead, are endocrine disrupters and also confirmed as being associated with obesity, which may indicate, along with environmental factors, the growing prevalence of overweight people (Grun and Blumberg 2006). The study by Sun et al (2017) demonstrated that chronic exposure to 0.05% lead (Pb) results in weight gain and insulin-specific resistance causing disorders are related to the metabolism.…”
Section: Analyzes Of the Animal Model 321 Evaluation Of Parametersmentioning
confidence: 99%